N-terminal proBNP plasma levels correlate with severity of mitral stenosis - Iltumur, K; Karabulut, A; Yokus, B; Yavuzkir, M; Taskesen, T; Toprak, N (I C R Publishers, 2005)
Background and aim of the study: Brain natriuretic peptide (BNP), a neurohormone, is secreted predominantly from the ventricular myocardium. Studies investigating BNP secretion in diseases affecting the right side of the heart are scarce. The relationship between N-terminal proBNP (NT-proBNP) and echocardiographic and clinical findings was studied in cases with isolated moderate to severe rheumatic mitral stenosis (MS), and in patients with previous mitral valve replacement (MVR). Methods: Thirty-two patients with MS (mean age 41.2 +/- 5.7 years), 20 with MVR (mean age 46.0 +/- 4.6 years) and 30 healthy individuals (mean age 40.3 +/- 4.9 years) were included in the study. In addition to NT-proBNP measurements, detailed transthoracic echocardiography was performed in all patients and healthy subjects. Results: Plasma levels of NT-proBNP were significantly higher in patients with MS than in those with MVR or in controls (99.8 +/- 12.7 versus 74.7 +/- 6.9 and 48.5 +/- 10.5 pg/ml, respectively; p < 0.0001 all groups). NT-proBNP levels showed a significantly greater increase in severe MS than in moderate MS (109.8 +/- 5.6 versus 88.3 +/- 7.6 pg/ml, p < 0.0001). NT-proBNP levels also were higher in MVR patients than in controls (74.7 +/- 6.9 versus 48.5 +/- 10.5 pg/ml; p < 0.0001). Although NT-proBNP levels did not correlate with left ventricular ejection fraction (LVEF) in patients with MS (r = -0.33; p > 0.05), there was a positive correlation with pulmonary artery pressure (r = 0.87; p < 0.001) and a negative correlation with mitral valve area (MVA) (r = -0.89; p < 0.0001). However, multivariate analysis identified only MVA as an independent correlate of NT-proBNP (P = -0.47; p = 0.02). Conclusion: In patients with rheumatic MS, NT-proBNP levels correlated positively with MS severity. Moreover, NT-proBNP levels increased significantly in patients with MS, but were significantly lower in those who underwent MVR.
Keywords: Brain Natriuretic Peptide; Pulmonary-Hypertension; Balloon Valvotomy; Heart-Failure; Atrial; Expression; Valvulotomy; Disease; Valve; Time